Comprehensive assessment of line‐/point‐focus combined scheme for concentrating solar power system. (5th February 2018) - Bai, Zhang; Sun, Jie; Liu, Qibin
Summary: The line‐/point‐focus combined scheme for concentrating solar power (CSP) system is proposed. For solar field, the parabolic trough (PT) or linear Fresnel (LF) is used as the line‐focus preheating and evaporation stages while the solar tower is used as the point‐focus superheating and reheating stages. The combined schemes benefit from the high concentration ratio of point‐focus technology and low cost of line‐focus technology. Particularly, the combined scheme guarantees the concentrated solar thermal energy matching the temperature requirement of steam generation process with less exergy loss. Performance and economic assessments have been performed for 50 MWe CSP system with two of the combined schemes, ie, PT (synthetic oil, SO) + Tower (molten salt, MS) and LF (direct steam generation, DSG) + Tower (DSG), as well as existing single schemes being the references, ie, PT (SO), LF (DSG), Tower (MS), and Tower (DSG). The comparative results show that the combined schemes are superior to liner‐focus schemes in efficiency and to point‐focus schemes in capital cost and scalability. Specifically, the PT (SO) + Tower (MS) system suggests the favorable potential in practical application with the highest annual net solar‐to‐electrical energy conversion efficiency of 16.07% and the reasonable levelized cost of electricity (LCOE) of 16.121 US cent/(kW·h). This work provides an alternative guidance for future development of the CSP technology.